Desenvolvimento de PVC reforçado com fibras de vidro longas para fabricação de produtos moldados - Grizzo, Leandro Henrique (2009)
This work presents a method of the long glass fiber reinforced PVC compound through incorporating continuous glass fibers with plasticized vinyl matrix prepared by wire coating process and pelletizing the coated roving (by cutting in the range 13 to 14 μm in length). The pellets (of long fiber glass incorporating in PVC) were mixed with granulated rigid PVC and this blend was fed directly into the injection-molding process machine. The direct injection molding in which composite parts are molded directly from the resin and reinforcement, eliminating the preliminary melt-compounding process - was achieved successfully. It was excellent because it reduced the number of processing steps that allowed cutting expenses, reduced the deterioration of the glass fibers length and reduced the possibility of PVC resins degradation happened. The vinyl composites long glass fiber reinforced PVC with 20 wt. %, exhibits excellent mechanical properties better than unreinforced rigid PVC. Its tensile modulus, flexural modulus and notched Charpy impact strength were twice that of unreinforced PVC even with the composites were formulated with a high quantity of plasticizer. The materials utilized to be compatibilizer (Vinisol OH e COOH) resulted in a moderately increased of tensile and flexural properties, moreover decreasing the notched Charpy impact strength of the vinyl composites. Therefore, they are not useful compatibilizer to PVC matrix based on balance of mechanical properties performance. All of the vinyl composites, formulated with or without compatibilizer, presented suitable dispersion of the glass fibers and good interfacial adhesion of fiber-matrix besides to be observed the presence of matrix adhered to the glass fiber s surface. In summary, long glass fiber reinforced PVC compound through incorporating by wire coating process was possible and it was created an innovating process of reinforcement into the vinyl area, in addition to the better mechanical properties achieved that allow PVC can be used in a unrecognized high-performance applications that was not possible before.